Fears of compassion magnify the harmful effects of threat of COVID‐19 on mental health and social safeness across 21 countries. (15th May 2021) - Matos, Marcela; McEwan, Kirsten; Kanovský, Martin; Halamová, Júlia; Steindl, Stanley R.; Ferreira, Nuno; Linharelhos, Mariana; Rijo, Daniel; Asano, Kenichi; Gregório, Sónia; Márquez, Margarita G.; Vilas, Sara P.; et al.
Abstract: Background: The COVID‐19 pandemic is a massive global health crisis with damaging consequences to mental health and social relationships. Exploring factors that may heighten or buffer the risk of mental health problems in this context is thus critical. Whilst compassion may be a protective factor, in contrast fears of compassion increase vulnerability to psychosocial distress and may amplify the impact of the pandemic on mental health. This study explores the magnifying effects of fears of compassion on the impact of perceived threat of COVID‐19 on depression, anxiety and stress, and social safeness. Methods: Adult participants from the general population ( N = 4057) were recruited across 21 countries worldwide, and completed self‐report measures of perceived threat of COVID‐19, fears of compassion (for self, from others, for others), depression, anxiety, stress and social safeness. Results: Perceived threat of COVID‐19 predicted increased depression, anxiety and stress. The three flows of fears of compassion predicted higher levels of depression, anxiety and stress and lower social safeness. All fears of compassion moderated (heightened) the impact of perceived threat of COVID‐19 on psychological distress. Only fears of compassion from others moderated the effects of likelihood of contracting COVID‐19 on social safeness. These effects were consistent across all countries. Conclusions: Fears of compassion have a universal magnifying effect on the damaging impact of the COVID‐19 pandemic on mental health and social safeness. Compassion focused interventions and communications could be implemented to reduce resistances to compassion and promote mental wellbeing during and following the pandemic.